Retail Development Trends Based on Digital Marketing - Saparova Mohira Alisher qizi (European Science Publishing, 2023)
In today's fast-paced digital age, the retail landscape is continuously evolving. Traditional brick-and-mortar stores are facing unprecedented challenges, and retailers are increasingly turning to digital marketing strategies to not only survive but thrive in this new era. In this article, we will explore the significant retail development trends that have emerged based on the integration of digital marketing strategies. These trends are reshaping the retail industry, influencing consumer behavior, and driving sales in innovative ways.
Keywords: Retail, Sales, Digital Marketing, E-commerce, Personalization, Customer-Centricity, Social Media, Influencer Marketing, Shoppable Posts, SEO.